Been wrong so long it feels like right - Mosley, Walter (Mosley, Walter. King Oliver novel, 2025)
"Joe King Oliver's beloved Grandma B has found a tumor, and at her age, treatment is high-risk. She's lived life fully and without regrets, and now has only a single, dying wish: to see her long-lost son. King has been estranged from his father, Chief Odin Oliver, since he was a young boy. He swore to never speak to the man again when he was taken away in handcuffs. But now, Grandma B's pure ask has opened King's heart, and through his hunt, he gains a deeper understanding of his father as a complicated, righteous man--a man defined by women, a man protected by women, a man he wants to know. Although Chief was released from prison years ago, he's been living underground ever since. Now, King must not only find his father, but prove his innocence, and protect the future of his entire family. Simultaneously, King finds himself in a moral bind. Marigold Hart, the wife of a powerful Californian billionaire, has gone missing, along with their seven-year-old daughter. Orr is brutish and dangerous, and King realizes after locating her that it's in her best interest to stay hidden. But are his motives pure? There is something magnetic about Marigold; he can't help but want her near"--